PENINGKATAN KETERAMPILAN MENULIS PARAGRAF MENGGUNAKAN PENDEKATAN COOPERATIVE LEARNING TIPE PICTURE AND PICTURE DI SEKOLAH DASAR - Utaminingsih, Tri; Halidjah, Siti; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study deals with the skills of writing paragraphs. Students tend not to be able to use the correct vocabulary, the use of punctuation is not right, the rules of writing are not in accordance with the EYD, can not pay attention to the relationship and continuity between the sentence one another so that a coherent writing that can be understood easily by the reader. The objective of the research is to describe the use of cooperative learning approach of picture and picture type to improve the writing skill of class III students. The form of research is classroom action research. The procedure of conducting classroom action research with four stages is planning, implementation, observation, and reflection. The average value of writing the first paragraph of the students in the first cycle of the first meeting is 50.69%, the second cycle of the second meeting increased 69.96%, the first cycle of the first meeting increased by 82.85% in the second cycle I increased by 2.21 to 85.06%.Cooperative learning approach of picture and picture type, can be applied at the time of learning process of Indonesian language because it can improve the skill of writing paragraph.Â Keywords: skill enhancement,Â  paragraph, cooperative learning tipe picture and picture